2003
DOI: 10.1007/s00213-002-1291-z
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of beer consumption in rats: acute anxiolytic and ataxic effects and withdrawal-induced anxiety

Abstract: These results are the first to our knowledge to show that rats will consume beer at levels that produce clear effects on anxiety and on motor co-ordination, and that will eventually produce behavioural signs of withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 46 publications
4
31
0
Order By: Relevance
“…The failure in the proper foot placement in AgNPs exposed rats implied that AgNPs might have potential to induce cerebellar ataxia-like disease. This is in correspondence with the ataxic effect in rats produced by beer consumption (Gallate et al, 2003). A decrease in activity or time spent in the center of the open field indicated the increase in animal anxiety or reduction in their exploration potential (Dulawa et al, 1999).…”
Section: Discussionsupporting
confidence: 71%
“…The failure in the proper foot placement in AgNPs exposed rats implied that AgNPs might have potential to induce cerebellar ataxia-like disease. This is in correspondence with the ataxic effect in rats produced by beer consumption (Gallate et al, 2003). A decrease in activity or time spent in the center of the open field indicated the increase in animal anxiety or reduction in their exploration potential (Dulawa et al, 1999).…”
Section: Discussionsupporting
confidence: 71%
“…The anxiolytic effects of ethanol have been extensively described (Bilkei-Gorzo et al, 1998;Colombo et al, 1995;Ferreira et al, 2000;Gallate et al, 2003;Hall et al, 1998;Martijena et al, 2001;Martin-Garcia and Pallares, 2005;Varlinskaya and Spear, 2002). In fact, although a previous study indicated that adolescent rats may be less sensitive than adults to the anxiolytic effects of ethanol (Varlinskaya and Spear, 2002), a recent study (Hefner and Holmes, 2007) showed that adolescent C57BL/6J mice exhibit increased sensitivity to anxiolytic-like effects of ethanol when compared to adults.…”
Section: Anxiolytic Effects During Adolescent Exposurementioning
confidence: 99%
“…Excessive alcohol consumption by anxious patients, presumably due to the anxiolytic properties of alcohol, has led to the hypothesis that anxiety could be a critical factor in the etiology of alcohol drinking (Colombo et al, 1995). The anxiolytic-like effects of ethanol associated with forced and acute administration (Bilkei-Gorzo et al, 1998;Ferreira et al, 2000;Hall et al, 1998;Martijena et al, 2001;Varlinskaya and Spear, 2002) or voluntary ethanol consumption (Colombo et al, 1995;Gallate et al, 2003) have been extensively described in different rodent tests. In addition, in contrast to the effect described during exposure, the occurrence of an anxiogenic-like effect during ethanol withdrawal has been reported (Kliethermes, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Acutely, ethanol alters memory (eg Givens, 1995), motor coordination (eg Gallate et al, 2003; but see Metz et al, 2003), and anxiety-related behaviors (eg Gallate et al, 2003;Langen et al, 2002;Ryabinin, 1998). Beside hyperlocomotion and hyperthermia, MDMA alters motor coordination (Marston et al, 1999), anxiety (Bhattacharya et al, 1998;Morley and McGregor, 2000;Sumnall et al, 2004), and cognitive functions (Braida et al, 2002;Ho et al, 2004;Marston et al, 1999; but see Ricaurte et al, 1993).…”
Section: Long-term Effects Of Etoh And/or Mdma On Behaviormentioning
confidence: 99%